Cartilage regeneration using decellularized cartilage matrix: Long-term comparison of subcutaneous and intranasal placement in a rabbit model - Bomhard, Achim von; Rotter, Nicole (Journal of cranio-maxillofacial surgery, 2019)
Autologous cartilage as donor tissue for various surgical reconstructions such as nasal septum regeneration is limited and associated with donor site morbidity. Our goal was to evaluate a new resorbable chondroconductive biomaterial made of decellularized porcine nasal septum cartilage compared with autologous native auricular cartilage as the gold standard. In order to examine the material and determine its long-term outcome further, we used subcutaneous implantation and septal implantation in an orthotopic rabbit model. In addition to non-seeded decellularized xenogenic cartilage, chondrocyte-seeded decellularized xenogenic cartilage was implanted as a septal replacement. After a three- or six-month period, the formation of newly synthesized cartilage extracellular matrix was evaluated immunohistochemically, whereas septal integrity and biocompatibility were evaluated histologically. The formation of the implanted neoseptum and form stability was analyzed by using 7-Tesla Magnetic Resonance Imaging. Good biocompatibility with no excessive rejection was demonstrated in all groups. Long-term stable and reliable septal reconstruction could be achieved in the study groups with or without cell seeding with autologous auricular chondrocytes. Autologous cell seeding was advantageous only with regard to septal perforations. Thus, cell seeding provides a benefit regarding long-term stability. However, because of slightly better biocompatibility, less pronounced septum deviation and the markedly lower effort involved, the non-seeded scaffold is favoured for possible clinical application.
Available online 25 January 2019
Gesehen am 13.05.2019